A Descriptive Study on the English Teachers’ Perception and Implementation of Curriculum 2013 at SMP Lab Hamzanwadi Pancor Lombok Timur - Mas, Dzoharat Nabilah (International Conference on Islamic Studies, 2020)
This study aims to determine how the English teachers implement Curriculum 2013 in the teaching and learning process in the classroom. The implementation of Curriculum 2013 requires teachers to organize effective learning. There are at least five things that need to be considered with regard to the organization of learning in the implementation of Curriculum 2013, the implementation of learning, procurement and development experts, utilization of expertise and resources of the community, as well as the development and structuring policy. The successful learning in the implementation of the Curriculum 2013 is the entire process of learning, competence and character formation of students is planned. For this purpose, the core competencies, basic competencies, material standards, indicators of learning outcomes, and time should be set in accordance with the interests of learning so that learners are expected to have the opportunity and the optimal learning experience. This study was a descriptive qualitative research. Descriptive because it describes about the characteristics of a phenomenon being studied, and this study described about the English teachers’ perception and implementation in the Curriculum 2013. There were two variables in this study, the first one were the English teachers’ perception and the second one was implementation of the 2013 curriculum. The participants in this study there were two English teachers’ in SMP Lab. Hamzanwadi Pancor. The data of the study used documentation of Curriculum 2013, interview, and observation. Descriptive qualitative data analysis used in this study was adopted from the qualitative data analysis techniques of Huberman (1994) that was data reduction, data display, and verification. The result of the study shows that the English teachers’ perception at SMP Lab. Hamzanwadi found difficulties to implement the Curriculum 2013 before they followed the socialization and after they followed the socialization the English teachers have been trying to be professional in designing affective and meaningful learning process, learning organizations, learning approach, procedure and establishing effective competencies, as well as setting criteria for success. Besides, the implementation of Curriculum 2013 has been done by the English teachers at SMP Lab. Hamzanwadi Pancor.